Synthesis of Bio-Cellulose Acetate Membrane From Coconut Juice Residues for Carbon Dioxide Removal From Biogas in Membrane Unit - Khamwichit, Attaso; Wattanasit, Sakkarin; Dechapanya, Wipawee (Frontiers in Energy Research, 2021)
The rapid growth of energy demand and consumption from fossil fuels has been of great concern since the last decade. Renewable energy, including biogas production from wastes, has been studied to ease up the energy crisis problems. This study aims to synthesize bio-cellulose acetate (CA) membranes from agricultural waste and to study its efficiency in the removal of CO2 from biogas. The bio-CA membranes were synthesized from acetylation of bacterial cellulose (BC) and obtained from coconut juice residues (CJRs). The results showed that both chemical and physical characteristics of the bio-CA membrane were compared with those of the chemical CA membranes. The CO2 removal capacity of the bio-CA membranes was tested in a membrane separation unit. The maximum CO2 selectivity of 29.53 was achieved when using the bio-CA membrane with a thickness of 0.05 mm under the feed pressure of 0.1 MPa. Thick CA membranes exhibited better CO2 selectivity performance, particularly at low operating pressure. However, the CO2/CH4 separation factor decreased in the high-pressure region, probably because of the plasticization of the gas components. Eco-efficiency was evaluated to determine the optimal process conditions. In terms of eco-efficiency, the results suggested that the optimal condition was a bio-CA membrane of 0.05-mm thickness and pressure of 0.1 MPa. The implication of this study is promoting a zero-waste environment in which the agricultural residues could be potentially used in the synthesis of high-value CA membranes for biogas purification applications in energy production.